Risk Factors for Ectopic Pregnancy: A Case-Control Study in Tertiary Care Hospitals of Jammu and Kashmir - Neha Mahajan; Rohit Raina; Pooja Sharma (Iberoamerican Journal of Medicine, 2021)
Introduction: An ectopic pregnancy occurs when a fertilized egg attaches somewhere outside the uterus.There are many risk factors for ectopic pregnancy. This study will help us to prepare a list of risk factors associated with ectopic pregnancy in our state. In addition, it will help implement a risk-reduction counseling program before conception, which will help us screen high-risk patients and reduce and manage ectopic pregnancy. Materials and methods: The present study was conducted in our department for two years, from August 2018 to July 2019. Cases included all patients with ectopic pregnancy admitted in labor. A total of 192 cases were taken, out of which 8 cases refused to participate in the study, so 184 patients were included in the study. Results: Patients with previous ectopic pregnancy have 6.34 times increased risk of a repeat ectopic pregnancy (odds ratio 6.34, confidence interval 1.40-28.77), and this association was highly significant (p = 0.006). The risk of ectopic pregnancy is 3.02 times increased (odds ratio 3.10; 95% confidence interval, 1.16-7.84) if the patient once had the pelvic inflammatory disease and is statistically significant (p = 0.01). The study also revealed that 17 (10.3%) patients with ectopic pregnancy had a history of tubal ligation or some other tubal surgery done in the past compared to 3 (2.2%) patients among controls, and this finding is statistically highly significant (p = 0.001). Conclusions: In the present study, we found that the main risk factors for incidence of ectopic pregnancy are prior ectopic pregnancy, prior tubal ligation, and prior pelvic/abdominal surgery. In addition, ectopic pregnancy was positively related to the previous history of ectopic pregnancy, abortion, cesarean section, and infertility. These findings can be helpful for early diagnosis of ectopic pregnancy to pursue proper medical therapy instead of unnecessarily surgical treatment.